2014
DOI: 10.4028/www.scientific.net/amr.955-959.1443
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hg on Jiaozhou BayWaters – The Change Process of the Hg Pollution Sources

Abstract: Based on investigation data in Jiaozhou bay waters from 1979 to 1985(absent of 1984), this paper tried to anylysis the horizontal distributions and pollution sources and characteristics of Hg in Jiaozhou Bay. The results showed that, the horizonal distributions of Hg in surface water of Jiaozhou Bay showed decreasing trends from river flow direct, and the major pollution source of Hg was point source, whose pollutants were transferred by stream discharge. Under the influences of point source pollution, the Hg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…As the rainy season was going on, the remaining Hg in land surface and river bed was decreasing, and the content and flux of Hg to waters and ocean were also decreasing in summer in July 1988. The seasonal variations of Hg contents in 1988 were consistent with other years during 1979-1986 [1][2][3][4][5][6][7][8][9][10][11], that was Hg contents in surface waters weer relative high in spring, and were relative low in summer, and were lowest in autumn. That was the seasonal variation's mechanism of Hg, and was also the terrestrial migration mechanism.…”
Section: Seasonal Variation's Mechanism Of Hgsupporting
confidence: 66%
See 1 more Smart Citation
“…As the rainy season was going on, the remaining Hg in land surface and river bed was decreasing, and the content and flux of Hg to waters and ocean were also decreasing in summer in July 1988. The seasonal variations of Hg contents in 1988 were consistent with other years during 1979-1986 [1][2][3][4][5][6][7][8][9][10][11], that was Hg contents in surface waters weer relative high in spring, and were relative low in summer, and were lowest in autumn. That was the seasonal variation's mechanism of Hg, and was also the terrestrial migration mechanism.…”
Section: Seasonal Variation's Mechanism Of Hgsupporting
confidence: 66%
“…For vertical distribution, the horizontal distributions of Hg contents in surface and bottom waters were consistent in July 1988, indicating that the relative high Hg contents were extending from the bay to open waters. The horizontal distributions of Hg contents in surface and bottom waters were confirming the migration process and mechanism in waters [10][11]. Hence, the settling process of Hg indicated that Hg was low soluble in waters and could be absorbed to suspending particular matters and transported from surface waters to bottom waters, and fixed to sedimentation in sea bottom finally.…”
Section: Seasonal Variation's Mechanism Of Hgmentioning
confidence: 52%
“…There are more than a dozen rivers entering the sea in Jiaozhou Bay, among which the Dagu River, Yang River and the Haibo River, Licun River and Loushan River in Qingdao City with larger runoff and sand content. These rivers are all seasonal rivers, and the river hydrological characteristics have obvious seasonal changes [12,13].…”
Section: The Natural Environment Of Jiaozhou Baymentioning
confidence: 99%
“…With the release of large amounts of Hg from land to the environment by many industries, Hg content has appeared on land, atmosphere, and oceans. The pollution degree and source of Hg content in the coastal waters has become everyone's concern [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Based on the survey data in 1993, the author studied the content, horizontal distribution and sources of Hg in the water body of Jiaozhou Bay.…”
Section: Introductionmentioning
confidence: 99%
“…Jiaozhou Bay is a semi-closed bay located in Shandong Province China, and has been polluted by various pollutants including Hg after the rapid increasing of industry the past three decades [10][11][12][13][14]. Using investigation data on Hg in April and July in Jiaozhou Bay, this paper analyzed the contents and horizontal distribution trends, and identified the rapid sedimentation processes of Hg.…”
Section: Introductionmentioning
confidence: 99%